2017
DOI: 10.1515/ijame-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Transport of MHD Couple Stress Fluid Through Peristalsis in a Porous Medium Under the Influence of Heat Transfer and Slip Effects

Abstract: An attempt has been made to examine the effects of magnetohydrodynamic couple stress fluid in peristaltic flow with porous medium under the impact of slip, heat transfer and wall properties. The expressions are obtained for temperature, coefficient of heat transfer and velocity. Influences of different parameters, the Hartmann number, Brinkman number and adaptability parameters on the temperature and warmth trade coefficient are discussed through outlines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Figure 6 shows the variation in the wall shear stress and it is observed that the wall shear stress decreases with increasing the magnetic parameter as reported in [24]. Figure 7 shows that wall shear stress decreases maximum at the throat of stenosis by increasing the values of the slip parameter h as noticed in [24,25,26,29]. Figure 8 shows that the effective viscosity and wall shear stress slightly decrease with body acceleration.…”
Section: Graphical Results and Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Figure 6 shows the variation in the wall shear stress and it is observed that the wall shear stress decreases with increasing the magnetic parameter as reported in [24]. Figure 7 shows that wall shear stress decreases maximum at the throat of stenosis by increasing the values of the slip parameter h as noticed in [24,25,26,29]. Figure 8 shows that the effective viscosity and wall shear stress slightly decrease with body acceleration.…”
Section: Graphical Results and Discussionmentioning
confidence: 66%
“…Malek and Horque [28] recently presented a theoretical study on the flow of blood through a stenosed artery with permeable wall taking into the consideration of the hematocrit level. Sankad and Nagathan [29] discussed the transport of an MHD couple stress fluid through peristalsis in a porous medium under the influence of the heat transfer and slip effects. Tripathi and Sharma [30] focused on the study of effects of heat and mass transfer on an arterial blood (with variable viscosity) flow in the presence of the applied magnetic field with chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Elangovan et al [24] investigated the Non-Newtonian blood movement for velocity slip with periodic body acceleration. Sankad and Nagathan [25] explained the peristaltic transport phenomena for MHD, heat transfer, thermal slip, wall properties, and porous medium for couple stress fluid mode. Ramesh and Devakar [26] studied the mass and heat transfer for peristaltic transport phenomena due to myometrial contractions occur in both symmetric and asymmetric channels.…”
Section: Introductionmentioning
confidence: 99%
“…Nayak and Dash [18] studied transient hydromagnetic flow of an electrically conducting couple stress fluid in a rotating frame of reference through a saturated porous channel under the influence of pulsatile pressure gradient. Sankad and Nagathan [19] examined the effects of MHD couple stress fluid in peristaltic flow with porous medium under the impact of slip, heat transfer and wall properties. MHD effects on peristaltic flow of a couple stress fluid in a channel with permeable walls was studied by Ramachandraiah et al [20].…”
Section: Introductionmentioning
confidence: 99%